Study on 3D shape and deformation measurement of a radiator fan based on high-speed binary defocused fringe projection - Qian XIONG; Lu CHEN; Qican ZHANG (Mechanical Engineering Journal, 2016)
The binary defocused fringe can overcome the nonlinear effect of an ordinary commercial digital projector and generate a good sinusoidal light field. In this paper, the binary fringe encoding method was chosen to complete the high-speed fringe projection using a DLP Lightcrafter 4500 model in dynamic Fourier transform profilometry, and then a camera was synchronously triggered to record the deformation fringes on the surface of a high-speed rotating radiator fan, whose time-changing 3D surface shape was reconstructed with Fourier fringe analysis. Further deformation analysis of the measured radiator fan blade and rotating shaft is helpful to improve the performance of the radiator. The experimental results on a tested radiator fan with the rotation speed of 4800rpm identified the validity of the presented setup, and this method can effectively expand the application of dynamic 3D shape measurement.